PENGELOLAAN SAMPAH RUMAH TANGGA DI NAGARI SALARE AIA KECAMATAN PELEMBAYAN - Mirnawati -; Ernawati Ernawati (JURNAL BUANA, 2022)
This study aims to discribe 1) houseold waste management in Salareh Aia village, 2) waste disposal or destruction behavior by housewives and working mothers in Salareh Aia village, and 3) factors that influence the behavior of housewives and mothers works on houseold waste management in the Salareh Aia village. This type of research is a qualitative descriptive. Using the informant selection techniques purposif sampling. Data collection technique using observation, interviews and documentation. The result showed that 1) management houseold wastein Salareh Aia village was still low, because the waste sorting was not carried out by housewives while wprking mothers who carried out waste sorting were only carried out by mothers who work as teachers and midwives. The waste management model yhat is carried out appliying the R2model (Reuse). 2) the behavior of culling or disposing of garbage by housewives and working mothers is three a) Dumping In water (throwing garbage into the river), b) Dumping (throwing garbage into canyons or ravines and roads), c) Incenaration (burning rubbish). 3) the factors the influebce housewives and working mothers in waste management in Salareh Aia village are three a) education, b) the role of government and community leaders, and c) facilities and infrastructure